2021
DOI: 10.15586/aei.v49i6.474
|View full text |Cite
|
Sign up to set email alerts
|

Practical protocol of the food allergy committee of the SEICAP on open oral food challenges to nuts

Abstract: Food allergy is rising rapidly among children, and allergy to nuts is one of the most prevalent allergies among them. The category “nuts and seeds” include several plant foods from different botanical families, very different from each other. It is not uncommon to detect co-sensitization to different nuts. However, true co-allergy is less frequent. Up to 80% of patients with positive skin prick tests or specific IgE without true history of reaction who avoid certain nuts, might tolerate them in an Oral Food Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Food allergies are an adverse health effect arising from a specific immune response that occurs reproducibly on exposure to a certain food, which is considered as a major public health concern. , Food allergies are classified into immunoglobulin E (IgE), non-IgE-mediated, and mixed-mediated (both IgE and non-IgE) reaction types. , It was reported that food allergies affected approximately 2–10% of the world’s population . The prevalence of food allergies has steadily increased in recent years, especially in industrialized countries, reaching 6% in Europe, USA, and Canada. In addition, the prevalence of food allergies in children under four years of age was on the rise, reaching 11% . According to the Food and Drug Administration (FDA) in the U.S., more than 90% of food allergies are triggered by nine major allergenic foods: tree nuts, shellfish, fish, egg, soybean, peanut, milk, wheat and sesame .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food allergies are an adverse health effect arising from a specific immune response that occurs reproducibly on exposure to a certain food, which is considered as a major public health concern. , Food allergies are classified into immunoglobulin E (IgE), non-IgE-mediated, and mixed-mediated (both IgE and non-IgE) reaction types. , It was reported that food allergies affected approximately 2–10% of the world’s population . The prevalence of food allergies has steadily increased in recent years, especially in industrialized countries, reaching 6% in Europe, USA, and Canada. In addition, the prevalence of food allergies in children under four years of age was on the rise, reaching 11% . According to the Food and Drug Administration (FDA) in the U.S., more than 90% of food allergies are triggered by nine major allergenic foods: tree nuts, shellfish, fish, egg, soybean, peanut, milk, wheat and sesame .…”
Section: Introductionmentioning
confidence: 99%
“…5−7 In addition, the prevalence of food allergies in children under four years of age was on the rise, reaching 11%. 8 According to the Food and Drug Administration (FDA) in the U.S., more than 90% of food allergies are triggered by nine major allergenic foods: tree nuts, shellfish, fish, egg, soybean, peanut, milk, wheat and sesame. 9 At present, many studies have demonstrated that various technologies induced the denaturation, degradation, and structural changes in proteins to cause the reduction of allergen contents and disruption/masking of epitopes for reducing the allergenicity in foods, involving heat treatment, 10,11 enzyme catalysis, 12,13 fermentation, 14,15 glycation, 16,17 irradiation, 18,19 polyphenol, 20,21 germination, 22,23 cold plasma bubbling, 24 and ultrasound, 25,26 etc.…”
Section: Introductionmentioning
confidence: 99%